ADDRESSING SYSTEM OF KINSHIP TERMS IN JAVANESE SOCIETY: A Case Study among Javanese People Living in Semarang - Krisnanda, Nabila (LANTERN (Journal on English Language, Culture and Literature), 2014)
In acommunication, people usuallyconveyan ideathroughlanguage. The relationshipbetweenaspeakerand ahearercan be reflectedin the useof language. One thingthatcandeterminethe relationshipbetweenspeakerandheareris an address forms. The use of address formsareboundby the local customs, manners, andcircumstances during conversation. Inthis study, Ilearnaddress formsin Javanese. Javanese people recognize certain codes for expressing politeness and respect. The speakers of Javanese language have special terms of address which they use when they talk to other people. It isclosely related to thesocialvaluesanddecencyinJavanesesociety.The purposes of this study are to know the actual use of addressing system of Javanese kinship terms by the society in daily conversations and to find out the factors that influence the use of address form in kinship terms of Javanese.The data used are the utterances from Javanese people that contain Javanese address forms in daily conversation. I use primary data because the data sources of this research come from the daily conversation of Javanese people in Semarang. The population of this research is all Javanese people living in Semarang. I use purposive random sampling technique. It means that, in deciding the samples that will be used, I have some criteria. The criteria are they are all Javanese people and they live in Semarang (Banyumanik, Tlogosari, Pasadena). They are twenty nine people and I divide them into six groups. The result of this study are the use of Javanese address form has been shifted. Javanese address forms relating to kinship terms have been used not only for the member of family but also for other people who do not have kinship terms or even strangers. Javanese address form also has been improved. There are some Javanese address forms are no longer used because its inferiority connotation meaning. Today, Javanese people tend to address mother as Ibu than Mak or Mbok, the elder sister as Mbak or Kak than Mbakyu, and uncle as Om than Paklik or Lik. Intimacy, solidarity, politeness, and power are the key factors that influence the use of address forms.Keywords: address forms, kinship terms, context